Regulation of pluripotency and reprogramming by RNA binding proteins - Li, Dan (Curr Top Dev Biol, 2020)
Embryonic stem cells have the capacities of self-renewal and pluripotency. Pluripotency establishment (somatic cell reprogramming), maintenance, and execution (differentiation) require orchestrated regulatory mechanisms of a cell’s molecular machinery, including signaling pathways, epigenetics, transcription, translation, and protein degradation. RNA binding proteins (RBPs) take part in every process of RNA regulation and recent studies began to address their important functions in the regulation of pluripotency and reprogramming. Here, we discuss the roles of RBPs in key regulatory steps in the control of pluripotency and reprogramming. Among RNA binding proteins are a group of RNA helicases that are responsible for RNA structure remodeling with important functional implications. We highlight the largest family of RNA helicases, DDX (DEAD-box) helicase family and our current understanding of their functions specifically in the regulation of pluripotency and reprogramming.